TANTANGAN DAN PELUANG DALAM PENERAPAN STRATEGI PEMASARAN PEDAGANG KAKI LIMA DI KOTA SERANG - Fidziah, Fidziah; Guli, Guli; Sucihati, Sucihati; Febrianata, Eka (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2024)
Marketing strategy is an essential business model in achieving desired marketing goals, including identifying target markets, preparing action plans, and appropriate resource allocation. Understanding the importance of marketing for business success is crucial in this context. The marketing process involves steps to understand consumer needs, create products or services that meet those needs, and convince potential buyers of the benefits of the product or service. This research uses qualitative methods, especially interviews, to explore information related to marketing strategies used by street vendors in Serang City. The research aims to understand how street vendors compete in the market and increase their income. Despite having limited knowledge about marketing strategies, street vendors are able to survive and achieve significant profits amidst high market competition